The challenges of Emergency Action Plan (EAP) implementation in construction project / Nur Naizatul Asyekin Mustafa - Mustafa, Nur Naizatul Asyekin (2021)
Emergency Action plan is well-known as a written document needed by certain Occupational Safety and Health Organization (OSHA) rules. An EAP’s role is to enable and facilitate employer and employee actions during emergencies at their workplace and to be prepared during emergency. Well-developed emergency action plans and thorough training, which to workers understand their roles and duties within the plan will result in fewer and less severe employee injuries, as well as less structural damage to the facility during emergencies. A sloppy strategy will often result in a disorganized evacuate or emergency response, miscommunications, injuries, and property destruction. Other than that, the problem arise from lack of awareness towards EAP can cause problem such as risk and natural disaster and increases the number of fatal. Thus, this research aimed to attempt the ascertain the challenges and strategies of Emergency Action Plan (EAP). There are objectives that helps to achieve the aim which are to identify the element of EAP in construction project, to identify the challenges of implementation of EAP in construction project and to recommend the strategies in implementing EAP in construction project. A quantitative research method is used and questionnaire as the data collection tool to achieve this objective of the research and the data was analyzed by SPSS software. There are 36 respondents who answered the questionnaire that has been distributed to constructors’ grade 7 in Kelantan. The result of the research study shows that the contractor agrees with Planning process as it has the highest level of challenges and highest suggestion strategy to be recommend is appoint skilled and knowledgeable safety manager at construction site.